An efficient merging scheme for prescribed skew clock routing. - Chaturvedi, R.
In ultra-deep submicron very large-scale integration (VLSI) designs, clock network layout plays an increasingly important role on determining circuit quality indicated by timing, power consumption, cost, power-supply noise, and tolerance to process variations. In this brief, a new merging scheme is proposed for prescribed nonzero skew routings which are useful in reducing clock cycle time, suppressing power-supply noise, and improving tolerance to process variations. This technique is simple and easy to implement for practical applications. Experimental results on benchmark circuits with both buffered and unbuffered routings exhibit large improvement on wirelength and buffer cost compared with other existing works.
Keywords: VLSI designs; Benchmark circuits; Buffered routing; Clock cycle time; Clock network layout; Design automation; Efficient merging scheme; Nonzero skew routings; Power consumption; Power-supply noise; Prescribed skew clock routing; Process variation tolerance; Timing performance; Unbuffered routings